Pengaruh Harga Terhadap Keputusan Pembelian Di Apotik MAMA Kota Depok - Isnurrini Hidayat Susilowati; Sarah Camelia Utari (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2022)
Each company always strives to maintain its customers in order to be able to follow competition between companies that are getting tighter. Customers are expected to continue making purchases. Prices are important, every price set by the company will result in the level of demand for the product to be different. The price specified by the company is exact and according to the purchasing power of consumers, the selection of consumers on a particular product will be imposed on the product. In this case also applies to product pricing sold at Depok Mama Pharmacy on purchasing decisions. In this study using a quantitative method with a questionnaire that was distributed to the customer of the Depok City Mama Pharmacy as a data retrieval and data processing tool used was SPSS 22. The results showed the price variables and purchasing decisions on the Depok City Mama Pharmacy had a very strong positive relationship and a positive price variable